Effect of Helicobacter Pylori infection on hematological values of pregnant women (Journal of Medical Sciences, 2023)
Helicobacter pylori is a gram-negative bacillus known to colonize the stomach and plays a role in gastric diseases even during pregnancy. In particular, this bacterium seems to be associated with hyperemesis gravidarum, a sever form of nausea and vomiting during pregnancy. The correlation among H. Pylori and pregnancy related disorders was mainly focused on iron deficiency anemia, thrombocytopenia, fetal malformation, miscarriage, preeclampsia and fetal growth restriction. Because the wide prevalence of H. pylori and its hematological affects for many pregnant women, Aim: this study was conducted on 70 samples of pregnant women affected with H. Pylori and not affected with H. Pylori in Brack Alshatii to know the affect of H. Pylori on hematological values. Materials and Method:  which include determined hemoglobin, hematocrit, red blood cells indices, white blood cells count, platelet count by complete blood count instrument, also determine anti body IgG to detect H. Pylori bacteria. Results:  In this study the arithmetic means for red blood cells, HB, Red blood cells indices for pregnant women with H. Pylori and without H. Pylori all in normal range excepting MCV, MCH for pregnant women without H. Pylori were below the normal range. The statistical analysis for these samples there were significant differences in MCH, and there were not significant differences in other hematological values. This study shows that arithmetic mean ± standard deviation for white blood cells, absolute number and percentage for lymphocyte, monocyte and granulocyte for pregnant women with H. Pylori and without H. Pylori all in normal range. Statistical analysis for these samples there were significant differences in lymph% and there were not significant differences (WBC, lymph#, Mid#, Gran#, Mid%, Gran%). Arithmetic mean ± Standard deviation of platelet within the normal range expecting PCT show decreasing in pregnant women with H. Pylori and without H. Pylori. Statistical analysis shows that there were significant differences in PCT and there were not significant differences in (PLT-MPV). Then this study shows that there was not important affecting of H. Pylori on hematological values in pregnant women with H. Pylori.